Integrated Approach for Text Hiding through Video using Steagnography and Visual Cryptography - Samanta, Sabyasachi; Saurabh Dutta; Gautam Sanyal (IJRDO -Journal of Computer Science Engineering, 2019)
Video steganography is a practice to hide information into carrier image files of video. Employment of the video steganography is more appropriate than the other carriers, not only for its magnitude but also the choice to pick the arbitrary image file(s). In this paper, we have worked on with a combination of encryption, steganography and visual cryptography. Initially, we have encrypted the data bits using one sorting based encryption technique. Then embedded that cipher text to some targeted frames of the video and also to some suitable nonlinear pixel positions of that image frames. Both of the encryption and embedding process have done by using distinct secret key. Next, some video shares have generated using color components of image and also key shares correspondingly. At the time of decryption, the video and key shares need to reschedule with proper order that make possible to retrieve hidden data bits from stego-video. The computational time for the decryption process is fewer than the other predictable video steganography methodologies. Without investigate all of the enclosures, cipher text are collected simply from the selected frame, pixel and bit positions which is selected by the secret key. Finally, the cipher text is decrypted by sorting based decryption algorithm.